THE EFFECT OF MOBILE BANKING SERVICE QUALITY ON CUSTOMER SATISFACTION OF BANK BSI IN LHOKSEUMAWE CITY - Weny Wardianingsih Hasibuan; Cut Sukmawati; Nursakinah Ritonga; Sufi; Maisyura (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The main problem in this study is the existence of obstacles and potential customer dissatisfaction with the quality of BSI Bank's mobile banking services in Lhokseumawe City, especially related to network speed. This study aims to analyze the Effect of Mobile Banking Service Quality on Customer Satisfaction at BSI Bank in Lhokseumawe City. This study uses a quantitative approach using nonprobability sampling, namely purposive sampling and obtained 96 respondents as research samples obtained from the Lemeshow formula. The data analysis method used in this study is simple linear regression, instrument testing, classical assumption testing, and hypothesis testing with the help of Microsoft Office Software Excel 2010 and SPSS Version 30 for windows. The results of this study indicate that the quality of mobile banking services has a significant effect on customer satisfaction at BSI Bank in Lhokseumawe City. This is evidenced by the results of the t-test which obtained a sig value for the mobile banking service quality variable of 0.001 <0.05 and the calculated t value is greater than the t-table value (11.113 > 1.6608). The influence of mobile banking service quality on customer satisfaction was 56.8%. Overall, customers rated BSI's mobile banking service quality positively, particularly in terms of ease of use, feature completeness, and privacy protection. However, there were still neutral ratings for technical reliability, indicating the need for improvements to boost customer trust and satisfaction.